Analisis Pengaruh Ketebalan dan Tipe Elektroda terhadap Tegangan dan Faktor Keamanan pada Sambungan Las Pipa - Mulyana, Mulyana; Al Adhim, Rizqi; Oleh, Oleh; Dirja, Iman (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Welded joining is a process of joining two or more similar metals by melting the area around the weld so that the metallurgical bonding of the weld metal occurs. In welding with filler metal, metals that have the same characteristics as the base metal are generally used. For welding thick pipes, notches and gaps are always made so that the filler metal can fill the area. The amount of filler metal will affect the strength of the weld. From the experimental results using E60xx and E70xx electrodes at a combined pressure of 60 bar, it gives good welding results at 1 mm filler filling. This result is in accordance with what is recommended by ASME.